Ethics and research in education: the ethical-epistemological (in)visibility of children in the informed consent (Práxis Educativa, 2023)
Of qualitative character, this text has as its essential objective to analyze, in the scope of research in education with children, the ethical-epistemological invisibility or visibility that is given to them. It is intended to know what ethical and epistemological modus operandi that adults, as researchers, demonstrate in relation to children, with regard to four specific dimensions that are intersected: 1) informed consent; 2) confidentiality, anonymity and privacy; 3) power relations between adults and children; 4) authorship of knowledge production. Given each of these aspects, it is sought to know if the researcher understands and assumes his/her fundamental task in this process of deep critical questioning and ethical-epistemological reflexivity that are imposed, being aware that there is no à la carte ethics ready to apply in any circumstance.Keywords: Ethics in research. Ethical-epistemological (in)visibility. Children.